The Effect of Career Calling on Learning Engagement Mediated by Career Adaptability on Final Students of the Faculty of Business Economics at State University of Padang - Zaki Andini; Yuki Fitria (International Journal of Economics and Management Research, 2025)
The development of higher education requires students to have career readiness and active involvement in the learning process in order to achieve academic and professional success. One important factor that influences learning engagement is career calling, which can increase students' intrinsic motivation in attending lectures. This study aims to analyze the effect of career calling on learning engagement mediated by career adaptability in final year students of the Faculty of Economics and Business, Padang State University. This study uses a quantitative approach with an explanatory research method. Data were collected through a Google Form questionnaire distributed to 280 students and analyzed using the SmartPLS v.4.0.9.9 application. The results of the study indicate that: (1) Career Calling has a positive and significant effect on Learning Engagement; (2) Career Calling has a positive and significant effect on Career Adaptability; (3) Career Adaptability has a positive and significant effect on Learning Engagement; and (4) Career Adaptability is able to positively and significantly mediate the effect of Career Calling on Learning Engagement. These findings reinforce the importance of developing career calling and career adaptability as strategies to increase student learning engagement before the transition to the world of work.